STRATEGI PEMBELAJARAN BAHASA ARAB PADA TINGKAT DASAR DI PAUD ISTIQLAL BANJARMASIN - Norilah; Farah Abdiyatuz Zakiyyah; Mushlih Hafizh Madani; Noor, Fatwiah (Institut Agama Islam Darul Ulum Kandangan, 2022)
The prime developmental period for children is their early years. A youngster between the ages of 0 and 6 is considered early childhood. Children are growing quickly at this time, especially in terms of language development. Learning a language should essentially involve learning to speak in that language, as well as studying Arabic, which may be done as early as feasible. However, learning foreign languages for young children definitely requires tactics in order to enhance learning achievement. This essay examines many methods for teaching Arabic to young children at PAUD Istiqlal Banjarmasin, including direct learning methods like memory, cognition, and compensatory strategies as well as indirect learning methods like metacognitive strategies.This paper is a field research that uses a qualitative approach and descriptive analysis. Keywords: Learning Strategy, PAUD, Arabic